ChemInform Abstract: Cascade Cyclizations of Acyclic and Macrocyclic Alkynones: Studies Toward the Synthesis of Phomactin A. Issue 9 (4th March 2014) - Ciesielski, Jennifer; Gandon, Vincent; Frontier, Alison J.
Abstract A study of the reactivity and diastereoselectivity of the Lewis acid promoted cascade cyclizations of both acyclic and macrocyclic alkynones is described.